2006
DOI: 10.1510/icvts.2006.140111
|View full text |Cite
|
Sign up to set email alerts
|

Minimized closed circuit/centrifugal pump extracorporeal circulation: an effective aid in coronary bypass operations in Jehovah's Witnesses

Abstract: Surgical treatment of a Jehovah's Witnesses continues to be a great challenge in cardiac surgery. Different strategies are used to minimize the risk for early mortality, prolonged intensive care unit stay and hospitalization, resulting from anemia. Minimized closed circuit extracorporeal circulations have been shown to reduce adverse effects of conventional CPB. Two patients underwent urgent coronary revascularization for triple-vessel disease. The miniECC (Stöckert) is a phosphorylcholine-coated device which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…If these results attain factual status, then for both medical and legal reasons, all efforts must be made to avoid recourse to blood transfusion not only amongst Jehovah’s Witnesses, but in all patients. A review of the existing literature on methods of blood transfusion indicates not only a discordance in practice amongst medical teams, but even amongst members of the same team: yet the morbidity-mortality rates are ubiquitous in the first 30 postoperative days [ 1 , 2 , 23 ]. Therefore, it appears desirable to replace these highly unsystematic methods of transfusion with a protocol of blood conservation which involves all members of the caring team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If these results attain factual status, then for both medical and legal reasons, all efforts must be made to avoid recourse to blood transfusion not only amongst Jehovah’s Witnesses, but in all patients. A review of the existing literature on methods of blood transfusion indicates not only a discordance in practice amongst medical teams, but even amongst members of the same team: yet the morbidity-mortality rates are ubiquitous in the first 30 postoperative days [ 1 , 2 , 23 ]. Therefore, it appears desirable to replace these highly unsystematic methods of transfusion with a protocol of blood conservation which involves all members of the caring team.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing cardiac surgery receive blood transfusion in 20-80% of cases. Certain studies suggest that half of these transfusions are unnecessary and can be avoided [ 1 , 2 ]. Furthermore, multivariate analyses have identified blood transfusion as an independent factor for mortality in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…3 10 Minimized cardiopulmonary bypass systems demonstrated significant benefits versus conventional CPB systems in terms of a reduction of the systemic inflammatory response and transfusion requirements, with resultant intact microcirculation. 11 28 Better myocardial protection 12,29,30 and less norepinephrine requirements 31 during surgery supported by a minimized system in comparison to a conventional system have been reported as well. Moreover, Anastasiadis et al 32 showed, in a meta-analysis, that the use of a minimized circuit reduces the total therapy cost by up to € 1.59 per patient.…”
Section: Introductionmentioning
confidence: 93%
“…If these results attain factual status, then for both medical and legal reasons, all efforts must be made to avoid recourse to blood transfusion not only amongst Jehovah's Witnesses, but in all patients. A review of the existing literature on methods of blood transfusion indicates not only a discordance in practice amongst medical teams, but even amongst members of the same team: yet the morbidity-mortality rates are ubiquitous in the first 30 postoperative days [1,2,23].…”
Section: ) Legal and Ethical Aspects Of Non Transfusionmentioning
confidence: 99%
“…Certain studies suggest that half of these transfusions are unnecessary and can be avoided [1,2]. Furthermore, multivariate analyses have identified blood transfusion as an independent factor for mortality in the long term.…”
Section: Introductionmentioning
confidence: 99%